The funerary and architectural history of an ancient Maya residential group: Group 5N6, Naachtun, Guatemala - Hemmamuthé Goudiaby; Philippe Nondédéo (Journal de la Société des Américanistes)
The majority of ancient Maya funerary contexts, at least those reported by archaeology, are residential in nature. This cultural specificity, while it renders the excavation process more complex, establishes a link between the grave and the surrounding buildings. In turn, this association allows for a very high chronological resolution in reconstructing the history of these residences and the lives of their inhabitants. At Naachtun (Petén, Guatemala), intensive excavations in the residential Group 5N6 over three field seasons yielded important data on the formation and evolution of an ancient Maya residential compound linked to the local elite. The results question the way the inhabitants envisioned and planned their living space and allow us to illustrate the existence of various funerary pathways among the ancient Maya.